Intelligent Electronic Devices - Zhao, Wenbing (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In a modern technological society, electronic engineering and design innovations are both academic and practical engineering fields that involve systematic technological materialization through scientific principles and engineering designs. Engineers and designers must work together with a variety of other professionals in their quest to find systems solutions to complex problems. Rapid advances in science and technology have broadened the horizons of engineering while simultaneously creating a multitude of challenging problems in every aspect of modern life. Current research is interdisciplinary in nature, reflecting a combination of concepts and methods that often span several areas of mechanics, mathematics, electrical engineering, control engineering, and other scientific disciplines. In addition, the 2nd IEEE International Conference on Knowledge Innovation and Invention 2019 (IEEE ICKII 2019) was held in Seoul, South Korea, on 12-15 July, 2019. This book, "Intelligent Electronic Devices", includes 13 excellent papers form 260 papers presented in this conference about intelligent electronic devices. The main goals of this book were to encourage scientists to publish their experimental and theoretical results in as much detail as possible and to provide new scientific knowledge relevant to the topics of electronics.